Interspecific differences in the bioaccumulation of arsenic of three Patagonian top predator fish: Organ distribution and arsenic speciation - Juncos, Romina (2019)
Interspecific differences in arsenic bioaccumulation and organ distribution (muscle, liver, kidney and gills) in three predator fish (creole perch, rainbow trout and brown trout) from a Patagonian lake impacted by volcanic eruptions were studied. Arsenic in fish organs were compared analyzing: 1) temporal (before and after volcanic eruption) and spatial (near and far from the volcano) influence of Puyehue-Cordón Caulle volcanic complex activity on arsenic concentrations; 2) the influence of growth (as total length), organ type and their interactions over arsenic accumulation; and 3) arsenic speciation and total arsenic relationship with carbon to nitrogen ratios (C:N), as a proxy of lipid presence, in fish muscle. In general, total arsenic concentrations in creole perch organs were 2–7 times higher than those recorded in the corresponding organs of salmonids. Arsenic was preferentially accumulated in liver and kidney in the three fish species. The influence of the volcanic activity over arsenic concentrations was more evident in creole perch: organs from creole perch captured closest to the volcano exhibited higher arsenic concentrations. Temporal variations were not so consistent. No clear relationship between arsenic and fish length was observed. Positive and linear relationship between arsenic in all pair of organs was found in creole perch, while rainbow trout showed a quadratic relationship between muscle and the remaining organs, indicating different arsenic assimilation-elimination relationships between organs and fish. The arsenic liver:muscle ratio in the three fish species was greater than 1, suggesting some level of arsenic stress. Arsenobetaine (AB) and dimethylarsinic acid (DMA) were the dominant arsenic species in muscle of these fish, having creole perch 3–4 times higher AB than rainbow trout. A positive relationship between C:N ratio and total arsenic concentrations was found, with higher C:N in creole perchs near the volcano. In terms of food safety, no inorganic arsenic compound were detected, therefore arsenic levels in fish from Lake Nahuel Huapi does not represent any health risk to consumers.